3D brain tumor segmentation scheme using K-mean clustering and connected component labeling algorithms - Moftah, Hossam M; Hassanien, Aboul Ella; Shoman, Mohamoud (2010 10th International Conference on Intelligent Systems Design and Applications, 2010)
In the recent years human brain segmentation in three-dimensional magnetic resonance imaging (MRI) has gained a lot of importance in the field of biomedical image processing since it is the main stage for the automatic brain disease diagnosis. In this paper, we propose an image segmentation scheme to segment 3D brain tumor from MRI images through the clustering process. The clustering is achieved using K-mean algorithm in conjunction with the connected component labeling algorithm to link the similar clustered objects in all 2D slices and then obtain 3D segmented tissue using the patch object rendering process.